Hak Politik Wanita dalam Al-Qur'an Perspektif Tafsir Fi Zhilalil Qur'an - Az Zahra Salsabila; Siti Chodijah; Eni Zulaiha (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss women's political rights in the Qur'an from the perspective of Tafsir fi Zhilalil Qur'an. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is Tafsir fi Zhilalil Qur'an. While the object of this research is the political rights of women in the Qur'an. The results of the research and discussion show that the Qur'an contextually forbids women to take part in the political sphere, while the Qur'an according to Sayyid Qutb's view in the book of Tafsir fi Zhilalil Qur'an encourages women to take part in the political sphere. The content of this interpretation is an inspiration for women to fight for their rights in the political realm. The conclusion of this study is that the discussion of several verses regarding women's political rights with the perspective of Tafsir fi Zhilalil Qur'an provides benefits for women activists to fight for their rights in the political realm.